Dissemination of the Acinetobacter baumannii isolates belonging to global clone 2 containing AbGRI resistance islands in a referral hospital - Ghazal Naderi; Mahla Asadian; Arash Seifi; Sedigheh Ghourchian; Malihe Talebi; Mohammad Rahbar; Alireza Abdollahi; Masoumeh Douraghi (Microbiology Spectrum, 2023)
ABSTRACT Acinetobacter baumannii strains belonging to global clone 2 (GC2) contain resistance islands (AbGRIs), which are composed of genes conferring resistance to older and newer antibiotics. Here, to locate these genes in AbGRIs, the GC2 strains from Tehran, Iran were examined. Among the 170 A. baumannii, 90 isolates were identified as GC2. Of the genes that confer resistance to older antibiotics, tetA(B), tetR(B) (tetracyclines), strA, and strB (aminoglycosides) were located in AbGRI1 of 65 GC2 isolates (72.2%). Of the other aminoglycosides, the aphA1b was located in AbGRI2-12b (63.6%), AbGRI2-12a (21.2%), or AbGRI2-1 (15.1%). The aacC1 and aadA1 genes were co-located within AbGRI2-1 (5.5%). The armA was located in AbGRI3-4 (77.7%) and AbGRI3ABI221 (22.2%). Of sulfonamides, the sul1 was located within AbGRI2-1 (5.5%). Of beta-lactams, the blaTEM was located in AbGRI2-12b (42%), AbGRI2-12a (14%), AbGRI2-1 (10%), or AbGRI2ABI257 (34%). The oxa23 gene conferring resistance to newer antibiotics (carbapenems) was located in AbaR4 (81.1%); of them, the AbaR4 was located within AbGRI1 in 45.2% of the isolates. This study showed that the GC2 isolates, which contained at least one AbGRI, disseminate in the hospital. Hence, it is likely that the AbGRIs play a significant role in conferring resistance to older and newer antibiotics in GC2 isolates from Iran. IMPORTANCE The majority of Acinetobacter baumannii isolates that are resistant to multiple antibiotics belong to one of the two major global clones, namely global clone 1 (GC1) and global clone 2 (GC2). The resistance islands, which contain variable assortments of transposons, integrons, and specific resistance genes, have been characterized in the genome of these GCs. In GC2 A. baumannii, the chromosomally located A. baumannii genomic resistance islands (AbGRIs) carry the genes conferring resistance to older and newer antibiotics. In this context, we tested whether GC2 isolates collected from a referral hospital carry the AbGRIs containing these genes. This study provided evidence for the circulation of the GC2 A. baumannii strains harboring AbGRI resistance islands between different wards of a referral hospital.